Household food insecurity and its association with overweight and obesity in children aged 2 to 14 years - Honorato Ortiz-Marrón; Maira Alejandra Ortiz-Pinto; María Urtasun Lanza; Gloria Cabañas Pujadas; Virginia Valero Del Pino; Susana Belmonte Cortés; Tomás Gómez Gascón; María Ordobás Gavín (BMC, 2022)
Abstract Background The objective was to estimate the prevalence of household food insecurity (HFI) depending on sociodemographic factors and its association with lifestyle habits and childhood overweight and obesity. Methods Data was collected from 1,938 children aged 2 to 14 years who participated in the "Study about Malnutrition" of the Community of Madrid. Weight and height were obtained through physical examination. Body mass index was calculated as weight/height2 (kg/m2) and the criteria of the WHO were used for determining conditions of overweight and obesity. The participants' parents answered a structured questionnaire about their diet, lifestyle (physical activity and screen time), and food insecurity. The diet quality was assessed with the Healthy Eating Index in Spain and food insecurity, defined as the lack of consistent access to sufficient food for a healthy life, was measured via three screening questions and the Household Food Insecurity Access Scale (HFIAS). Odds Ratios (ORs) and Relative Risk Ratios (RRRs) were estimated using logistic regression models and adjusted for confounding variables. Results The overall prevalence of HFI was 7.7% (95% CI: 6.6‒9.0), with lower values in children 2 to 4 years old (5.7%, 95% CI: 4.0‒8.1) and significantly higher values in households with low family purchasing power [37.3%; OR: 8.99 (95% CI: 5.5‒14.6)]. A higher prevalence of overweight (33.1%) and obesity (28.4%) was observed in children from families with HFI, who presented a lower quality diet and longer screen time compared to those from food-secure households (21.0% and 11.5%, respectively). The RRR of children in families with HFI relative to those from food-secure households was 2.41 (95% CI: 1.5‒4.0) for overweight and 1.99 (95% CI: 1.2‒3.4) for obesity. Conclusion The prevalence of HFI was high in the paediatric population, especially in households with low family purchasing power. HFI was associated with lower diet quality and higher prevalence of childhood overweight and obesity. Our results suggest the need for paediatric services to detect at-risk households at an early stage to avoid this dual burden of child malnutrition.